2021
DOI: 10.1101/2021.07.24.453587
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolution of a chordate-specific mechanism for myoblast fusion

Abstract: The size of an animal is determined by the size of its musculoskeletal system. Myoblast fusion is an innovative mechanism that allows for multinucleated muscle fibers to compound the size and strength of individual mononucleated cells. However, the evolutionary history of the control mechanism underlying this important process is currently unknown. The phylum Chordata hosts closely related groups that span distinct myoblast fusion states: no fusion in cephalochordates, restricted fusion and multinucleation in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…A recent study has suggested that MYMK and MYMX have coevolved in the vertebrates [ 119 ]. These observations indicate that MYMK and MYMX evolved together for myoblast fusion, parallel to the emergence of sarcomeric muscle and EC coupling in this lineage [ 120 ].…”
Section: Divergent Fusion Machinery Between Amniotes and Anamniotesmentioning
confidence: 99%
“…A recent study has suggested that MYMK and MYMX have coevolved in the vertebrates [ 119 ]. These observations indicate that MYMK and MYMX evolved together for myoblast fusion, parallel to the emergence of sarcomeric muscle and EC coupling in this lineage [ 120 ].…”
Section: Divergent Fusion Machinery Between Amniotes and Anamniotesmentioning
confidence: 99%
“…No Myomixer orthologue was found in non-vertebrate chordate groups, indicating that Myomixer is a vertebrate-specific gene with myoblast fusion functions, conserved from lampreys to humans. 92 In response to muscle injury (CTX), Myomixer expression is immediately increased and is essential for satellite cell fusion, demonstrating an important function during the process of muscle regeneration. Besides, Myomixer-knockout mice embryos have lack of skeletal muscle and absence of multinucleated myofibres, which Myomixer being required for skeletal muscle development in vivo and in vitro.…”
Section: Microprotein and Myoblast Fusionmentioning
confidence: 99%
“…Although lamprey Myomixer is a 583‐aa protein and exhibits sequence divergence, it is capable to replace human Myomixer and promote myoblast fusion. No Myomixer orthologue was found in non‐vertebrate chordate groups, indicating that Myomixer is a vertebrate‐specific gene with myoblast fusion functions, conserved from lampreys to humans 92 …”
Section: Microproteins In Muscle: What Do We Know?mentioning
confidence: 99%